Time-reversible always stable predictor-corrector method for molecular dynamics of polarizable molecules - Kolafa, Jirí (Journal of computational chemistry, 2004)
An improved method for classic molecular dynamics of polarizable molecules is proposed. The method uses a predictor, one evaluation of the electrostatic field per integration step, and relaxation (damping). The self-consistent solution is approximated with error of the second order (with respect to the timestep). The time reversibility (long-time energy conservation) error is of the (2n - 1)th order, where n is the predictor length. The method is easy to implement, efficient, accurate, and suitable for any model of polarizability.